Association of Body Mass Index and Age with Positive Receptors Expression and Metastasis Status Subtypes in Iraqi Women with Breast Cancer - H. Kzar, Hamzah; E. Al-Gazally, Moaed; A. Wtwt, Moshtak (International Journal of Psychosocial Rehabilitation, 2020)
Background: Breast cancer (BC) is a heterogeneous disease witch produce from a number of genetic and epigenetic risks that lead to dysregulation of cell growth, circumvention of apoptosis, and development of the ability to invade the underlining tissue through the basement membrane. Aim: To assessment the association of BMI and age with positive receptors and metastasis status subtypes expression in Iraqi women of BC and determine the ERA and ERB and investigated the impact of those biomarkers alteration on the prognosis of patients with BC. Methods: This case-control study involved on 120 women with BC and same number as control group. Estimation of ERA and ERB were based on sandwich- ELISA. Results: The results examined that age and BMI of women with BC were significant associated with positive expression of ER and PR (p-value 0.05). The results referred to a significant effects of age and BMI on expression of ER and PR in women with BC (OR=1.25 CI95%=0.49-3.51, OR=1.60 CI=0.61-4.16) (OR=1.4 CI95%=1.4-3.6, OR=1.83 CI95%=0.69-4.87), respectively. The results suggested the significant increase in incidence of IDC type of BC compare to ILC in women with (BMI ≥ 25) Conclusion: Assessment of ERA and ERB are useful in diagnosis and following up of women with BC in different ER, PR, ,Her-2, and in different histological grades.